2010
DOI: 10.4314/bcse.v24i3.60787
|View full text |Cite
|
Sign up to set email alerts
|

<b>Mass concentrations and elemental composition of urban atmospheric aerosols in Addis Ababa, Ethiopia</b>

Abstract: in urban and peri-urban areas of Addis Ababa, Ethiopia, with the aim to assess the spatial and temporal aspects of total suspended particulate (TSP) and particulate matter with aerodynamic diameter less than 10 µm (PM10) and their composition in terms of metallic elements. Sixty six filter samples were collected from seven distinct sites using I.O.M. multi fraction dust samplers and fiber glass filter papers. The mass of each particulate matter sample was measured gravimetrically and the composition of PM10 sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Entrained dust is expected to contribute more to particulate loadings in an environment such as Lagos with many unpaved roads and walkways. PM mass concentrations in this study were similar to those reported for urban sites in Ethiopia [25], Morrocco [26] and Kenya [27]. Table 1 displayed average concentrations, enrichment factor (EF) and pollution indices (PI) of twenty-four elements (Na, Mg, Al, Si, P, S, Cl, K, Ca, Ti, V, Cr, Mn, Fe, Ni, Cu, Zn, Se, Br, Rb, Sr, Zr, Cs and Pb) detected in both particulate sizes.…”
Section: Mass Concentrationssupporting
confidence: 77%
See 1 more Smart Citation
“…Entrained dust is expected to contribute more to particulate loadings in an environment such as Lagos with many unpaved roads and walkways. PM mass concentrations in this study were similar to those reported for urban sites in Ethiopia [25], Morrocco [26] and Kenya [27]. Table 1 displayed average concentrations, enrichment factor (EF) and pollution indices (PI) of twenty-four elements (Na, Mg, Al, Si, P, S, Cl, K, Ca, Ti, V, Cr, Mn, Fe, Ni, Cu, Zn, Se, Br, Rb, Sr, Zr, Cs and Pb) detected in both particulate sizes.…”
Section: Mass Concentrationssupporting
confidence: 77%
“…In Tables 4 and 5 ) for Addis Ababa [25] and Kenitra [26] respectively. This could be due to many reasons such as geographical locations, time, height and duration of sampling.…”
Section: Comparison Of Elemental Concentrationsmentioning
confidence: 99%
“…Published and unpublished data from Ethiopia has shown that ambient fine PM (PM 2.5 —PM ≤ 2.5 microns in aerodynamic diameter) are high and above the Air Quality Guidelines (AQG) of the World Health Organization (WHO) [ 3 , 4 , 12 ]. Prior studies, for instance, in Addis Ababa [ 5 , 13 ] reported that PM 10 concentrations were increasing and above the annual value of WHO air quality guidelines [ 14 ] and Ethiopian standards [ 15 ]. However, only a few studies characterizing the sources of ambient air pollution have been carried out in large cities of sub-Saharan Africa where ambient air pollution appears to be worsening.…”
Section: Introductionmentioning
confidence: 99%
“…Information on source apportionment and chemical compositions of particulate matter (PM) and other air pollutants is scarce. There are a few reports that cover source apportionment of PM2.5 and PM10 sources in AA (Etyemezian et al, 2005;Gebre et al, 2010;Tefera et al, 2020), though there are no published sources identifying the PM and other pollutant sources nor CO2 via receptor modeling or principal component analysis.…”
Section: Introductionmentioning
confidence: 99%